Cover Picture: Stabilization of Tetrahedral P4 and As4 Molecules as Guests in Polymeric and Spherical Environments (Angew. Chem. Int. Ed. 41/2013). Issue 41 (2nd September 2013) - Schwarzmaier, Christoph; Schindler, Andrea; Heindl, Claudia; Scheuermayer, Sabine; Peresypkina, Eugenia V.; Virovets, Alexander V.; Neumeier, Maria; Gschwind, Ruth; Scheer, Manfred
<x xml:space="preserve">Abstract</x> A new chapter in the history of arsenic has been opened up by M. Scheer et al. in their Communication on page 10887 ff. Long after the discovery of grey and yellow arsenic by Albertus Magnus and Anton Bettendorff, the structure of As4 has finally been described by X‐ray crystallographic techniques. Highly reactive yellow arsenic was embedded in a polymeric matrix, which minimizes molecular motion and therefore allows the determination of the As–As bond length.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>